Do Firm‐Specific Stock Price Crashes Lead to a Stimulation or Distortion of Market Information Efficiency?* - Kim, Jeong‐Bon; Lee, Edward; Zhu, Zhenmei (Judy) (Contemporary Accounting Research, 2022)
Unlike prior research that focuses on determinants of firm-specific stock price crashes (SPCs), we study the consequences of SPCs on market information efficiency. The tension underlying our research question stems from two competing explanations. As an unanticipated shock, an SPC could stimulate (distort) information efficiency by triggering investor rational attention (opinion divergence). Our identification strategy involves a difference-in-differences analysis in which SPC firms in the treatment sample are propensity score matched with non-SPC firms in the industry-peer control sample, as well as placebo tests for falsification. Consistent with the stimulation effect, we find an increase of the earnings response coefficient and a decrease in post-earnings announcement drift, from the pre- to post-SPC period, for SPC firms, but not for non-SPC firms. Further analyses reveal that SPC firms attract increased investor attention, as reflected in greater analyst coverage and more investor access to firms' online financial filings following such an event. Using mutual fund flow redemption pressure based on hypothetical sales as an exogenous shock to SPCs, we provide evidence corroborating our causal interpretation of the main findings. Collectively, the evidence suggests that SPCs can attract increased investor attention, bringing about positive externalities by stimulating market information efficiency.